Comparison of biochemical characterizations with PCR amplification in identifi cation of Malassezia species isolated from pityriasis versicolor and healthy volunteers - Intayot, Proawpilart; Youngchim, Sirida (Biomedical Sciences and Clinical Medicine, 2024)
The aim of this research was to determine the correlation between biochemical features and a molecular method in the identifi cation of Malassezia spp. To achieve this study, 173 isolates of Malassezia spp. were collected from 8 patients with pityriasis versicolor and 165 healthy volunteers. Differentiation of Malassezia spp. was performed by using biochemical test and PCR amplifi cation. The agreement between biochemical features and PCR amplifi cation was found 73.41% (127/173) in the identifi cation of M. sympodialis, M. furfur, M. dermatis and M. slooffi ae. In particular for M. furfur and M. sympodialis, the higher percentages of the agreement between these two methods were found 81.94 and 77.63%, respectively. In addition, 46 isolates of Malassezia spp. were differentiated by PCR amplifi cation only and then confi rmed by genomic sequencing. Six species of Malassezia including M. sympodialis (36.95%), M. furfur (28.26%), M. dermatis (21.74%), M. slooffi ae (4.35%), M. globosa (4.35%), and M. japonica (4.35%), were detected. These fi ndings suggest that PCR amplifi cation can be used as a potential tool in identifi cation of Malassezia spp. when compared with the biochemical method. However, the biochemical studies are suitable for the presumptive identifi cation of Malassezia species where molecular methodologies are not available.